Charged Particle Optics Theory An Introduction - Groves, Timothy R. (Taylor & Francis, 2015)
Charged Particle Optics Theory: An Introduction identifies the most important concepts of charged particle optics theory, and derives each mathematically from the first principles of physics. Assuming an advanced undergraduate-level understanding of calculus, this book follows a logical progression, with each concept building upon the preceding one. Beginning with a non-mathematical survey of the optical nature of a charged particle beam, the text: Discusses both geometrical and wave optics, as well as the correspondence between them Describes the two-body scattering problem, which is essential to the interaction of a fast charged particle with matter Introduces electron emission as a practical consequence of quantum mechanics Addresses the Fourier transform and the linear second-order differential equation Includes problems to amplify and fill in the theoretical details, with solutions presented separately Charged Particle Optics Theory: An Introduction makes an ideal textbook as well as a convenient reference on the theoretical origins of the optics of charged particle beams. It is intended to prepare the reader to understand the large body of published research in this mature field, with the end result translated immediately to practical application.